Influence of benzyltriethylammonium chloride on biocorrosion activity of consortium bacteria from tropical crude oil - Mohd Nazri Idris; Abdul Razak Daud; Nur Akma Mahat; Mohd Hafizuddin Ab Ghani; Fathul Karim Sahrani; Norinsan Kamil Othman (Universiti Kebangsaan Malaysia, 2015)
The performance of pipeline system used in petroleum industry is crucially declined by natural microbial activities and demanding extra operational cost. Requirement on high capability of functional substances is attracting worldwide research interest. The aim of this paper was to study the effectiveness of benzyltriethylammonium chloride (BTC) on reducing the activity of a consortium bacteria consisting of sulfate-reducing bacteria (C-SRB). C-SRB was isolated from tropical crude oil and enumeration of this consortium was measured by viable cell count technique. The effectiveness of BTC was calculated from potentiodynamic polarization method and biofilm analysis was performed by scanning electron microscope. The viable cell count technique indicated that the maximum growth of C-SRB was approximately 160 trillion CFU/mL at 7 days incubation period. BTC was capable of reducing biocorrosion activity due to adsorption process and mitigating SRB species. Biofilm analysis has proven that C-SRB activity is minimized due to less presence of bacterial growth, extracellular polymeric substances and corrosion product. In conclusion, BTC is capable to inhibit C-SRB activity on biocorrosion of carbon steel pipeline.